IL-1β and IL-1Ra Variant Profiles in Turkish Patients with Diabetic Peripheral Neuropathy - Nursal, Ayse F.; Inanir, Ahmet; Rustemoglu, Aydın; Uzun, Suheyla; Sahin, Kubra; Yigit, Serbulent (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2019)
Background: Diabetic peripheral neuropathy (DPN) is one of the most common complications of Type 2 diabetes mellitus (T2DM). This study was conducted to investigate the possible association between interleukin-1β (IL-1β) rs16944 /IL-1 receptor antagonist (IL-1Ra) VNTR variants and genetic susceptibility to DPN in a Turkish cohort. Methods: A total of 200 subjects were enrolled in this study, 98 patients with DPN and 102 cases of age and sex-matched healthy controls. Genotyping was performed for all individuals using PCR-RFLP analysis. Results: IL-1β rs16944 CC genotype had a 3.20-fold increased risk for DPN (p=0.0003, OR=3.20, 95% Cl:1.72-5.96). IL-1β rs16944 CT genotype was higher in healthy control than patients (p=0.004). IL-1β rs16944 C allele was higher in the patient group compared to controls while T allele was lower in patients than controls (p=0.003). IL-1Ra VNTR a1/a1 and a2/a2 genotypes were lower in DPN patients while a1/a2 genotype was higher in patients (p=0.045). The patients carrying a1/T haplotype had decreased risk of DPN than control groups (p=0.004). The patients carrying a2/a2 genotype had lower HDL level (p=0.039). The subjects carrying a2/a2 genotype had higher total cholesterol level while the subjects carrying a1/a2 genotype had lower total cholesterol (p=0.026 and p=0.037, respectively). IL-1Ra a1 allele was associated with higher HDL level (p=0.041). Conclusion: Findings of this study indicated that the IL-1β rs16944 and IL-1Ra VNTR variants are probably to be associated with susceptibility DPN risk in a Turkish cohort.
Keywords: DPN risk